MOTIVASI TAIWAN MELARANG IMPOR PRODUK INDOMIE ASAL INDONESIA PADA TAHUN 2010 - Amalya Lovinna; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
In 7th October 2010, Taiwan made announced to banned on Indomie Indonesia instant noodle product. Taiwan claims that Indomie is had certain health problem issues, that contains two preservatives that are prohibited namely methyl p-hydroxybenzoate and benzoic acid. Two elements should only be used to make cosmetics. Due to the CODEX standards, prove that Indomie is safe to consume, the elements who use in the noodles is on the small quantity. Rather than that, the differences in food safety standards applied in each country said that Taiwan doesn’t accept any kind and quantity of nipagin, against to that standards, PT Indofood CBP then says that they already made two kind of instant noodles due to the international and domestic standards, and as long as they importer instant noodle, it is the first time they had protest about the product. The research use Competitive Advantage which has been revealed by Michael E. Porter. This research is qualitative research by using using primer and secondary file, the used technique is collecting file which is used by library observation, journal, and website The result of this research prove that there’s no relevant reason owned Taiwan to impose ban on Indomie Indonesia instant noodle, after re-investigation, and directly meeting in 13th October 2010. In 9th December 2010, Taiwan re-announced that all the Taiwan’s data and evidence is a mistaken. The only reason Taiwan’s had is related to economy interest and political interest Keywords: Motivation, Trade Relations, banned on instant noodles, Protectionism